Implementation of a Meningitis Care Bundle in the Emergency Room Reduces Mortality Associated With Acute Bacterial Meningitis. (September 2015) - Viale, Pierluigi; Scudeller, Luigia; Pea, Federico; Tedeschi, Sara; Lewis, Russell; Bartoletti, Michele; Sbrojavacca, Rodolfo; Cristini, Francesco; Tumietto, Fabio; Di Lauria, Nicoletta; Fasulo, Giovanni; Giannella, Maddalena
Background: Prompt administration of antibiotics, adjunctive steroid therapy, and optimization of antibiotic delivery to cerebrospinal fluid (CSF) are factors associated with improved outcome of patients hospitalized for acute bacterial meningitis (ABM). However, the impact of a bundle of these procedures has not been reported.Objective: To assess mortality and neurological sequelae at hospital discharge in a cohort of patients with ABM managed according to a predefined bundle.Methods: Prospective study of all the patients hospitalized for ABM in two provinces of Northern Italy, over two consecutive periods (2005-2009, 2010-2013). The bundle included: i) supportive care if needed; ii) immediate administration of dexamethasone and 3rd generation cephalosporin; and iii) addition of levofloxacin if turbid CSF. Patients managed according to the bundle were compared with a historical group of patients cared for ABM before the bundle was implemented.Results: Overall, 85 patients with ABM were managed according to the bundle and were compared with 92 historical controls. In-hospital mortality rates for bundle and control group were 4.7% and 14.1% (p=0.04). Among survivors, 13.5% and 18.9% (p=0.4) of bundle and control-group patients presented neurological sequelae. The only variable associated with mortality at multivariate analysis was ICU admission (HR 3.65). After adjusting for ICU admission, patients managed according with the ABM bundle had significantly lower mortality rate compared to historical controls.Conclusions: Use of a bundled protocol and antibiotics with excellent CSF penetration for the initial management of ABM in emergency department is feasible and associated with significant reduction in mortality.